2017
DOI: 10.1002/etc.3816
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the toxicity of Headline® fungicides to terrestrial stage toads

Abstract: Amphibians are susceptible to exposure from contaminants via multiple pathways. Pyraclostrobin fungicides have been shown to be toxic to terrestrial amphibians at environmentally relevant concentrations; however, these studies did not account for factors that may influence exposure and effects, such as fungicide formulation, age of the individual, exposure route, and physiological state of the individual. We examined Headline® and Headline AMP® fungicide toxicity to adult Anaxyrus cognatus and Anaxyrus woodhou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Likewise, Mitchkash et al (2014) recorded effects on the best run time of spotted salamander ( Ambystoma maculatum ) after carbaryl exposure. In contrast, Webber et al (2010) and Cusaac et al (2017) did not find any effects on feeding behavior after exposure of juvenile Great Plains toads ( Anaxyrus cognatus ) to carbaryl and pyraclostrobin.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Likewise, Mitchkash et al (2014) recorded effects on the best run time of spotted salamander ( Ambystoma maculatum ) after carbaryl exposure. In contrast, Webber et al (2010) and Cusaac et al (2017) did not find any effects on feeding behavior after exposure of juvenile Great Plains toads ( Anaxyrus cognatus ) to carbaryl and pyraclostrobin.…”
Section: Discussionmentioning
confidence: 88%
“…For logistical reasons, formulations could not be tested at the same time, but they were tested within 2 wk of each other. In a pretest, 3 individuals were exposed to soil contaminated with 100% of the maximum recommended field rate of Folpan WDG (FR max = 3.6 kg/ha), which led to 100% mortality after 24 h. To additionally consider pesticide exposure mitigation by interception of crops (Cusaac et al 2017), half of the maximum recommended field rate (50% FR max = 1.6 kg Folpan WDG/ha) of Folpan WDG was applied to the soil, which corresponds to 0.64 kg a.i./ha with an application volume of 200 L/ha. To allow comparison of effects induced by Folpan WDG and Folpan suspension concentrate, equal amounts of the active ingredient were applied for Folpan suspension concentrate, resulting in a field rate of 1.28 L Folpan suspension concentrate/ha with an application volume of 200 L/ha.…”
Section: Soil Exposure Testsmentioning
confidence: 99%
“…While in Cusaac et al (2017), the authors observed that dehydration did not influence mortality when amphibians were exposed to Headline AMP. In the current study, wholebody concentrations for each pesticide were shown to decrease with increasing dehydration time (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…There is a need for more mixture and multimedia experiments in wildlife ecotoxicology (Glinski et al, 2019). Semifield experiments using enclosures have been used to quantify multimedia exposure under controlled but realistic conditions (Cusaac et al, 2015(Cusaac et al, , 2017Vyas et al, 2007). Use of complex effluents or contaminated soils in laboratory and field testing provides an opportunity to assess both bioavailability and uptake of weathered mixtures (Panico et al, 2022).…”
Section: Optimization and Improvement Of Experimental Designs In Appl...mentioning
confidence: 99%